Juvenile angiofibroma: a case report - Tiago Lourenço Coelho; Hugo Figueiredo; Ana Beatriz Ramada; Davide Lourenço Marques; Ricardo Caiado; Jorge Migueis; Luis Filipe Silva (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Juvenile Angiofibroma is a rare pathology, with high associated morbidity.